Optical emission from focused ion beam milled halide perovskite device cross‐sections. Issue 6 (3rd February 2022) - Kosasih, Felix U.; Divitini, Giorgio; Orri, Jordi Ferrer; Tennyson, Elizabeth M.; Kusch, Gunnar; Oliver, Rachel A.; Stranks, Samuel D.; Ducati, Caterina
Abstract: Cross‐sectional transmission electron microscopy has been widely used to investigate organic–inorganic hybrid halide perovskite‐based optoelectronic devices. Electron‐transparent specimens (lamellae) used in such studies are often prepared using focused ion beam (FIB) milling. However, the gallium ions used in FIB milling may severely degrade the structure and composition of halide perovskites in the lamellae, potentially invalidating studies performed on them. In this work, the close relationship between perovskite structure and luminescence is exploited to examine the structural quality of perovskite solar cell lamellae prepared by FIB milling. Through hyperspectral cathodoluminescence (CL) mapping, the perovskite layer was found to remain optically active with a slightly blue‐shifted luminescence. This finding indicates that the perovskite structure is largely preserved upon the lamella fabrication process although some surface amorphisation occurred. Further changes in CL due to electron beam irradiation were also recorded, confirming that electron dose management is essential in electron microscopy studies of carefully prepared halide perovskite‐based device lamellae. Research Highlights: Cathodoluminescence is used to study the emission of focused ion beam milled perovskite solar cell lamellae. The perovskite remained optically active with a slightly blue‐shifted luminescence, indicating that the perovskite structure is mostly preserved. Abstract : Normalized perovskite emission spectra from (red) top‐view PL, (orange) top‐view cathodoluminescence (CL), (green) first cross‐sectional CL scan, and (blue) second cross‐sectional CL scan. As the signal‐to‐noise ratio for the second cross‐sectional CL scan is relatively low, normalization was performed on the Gaussian fit (blue line) rather than on the data points.